Synthesis And Characterization of Activated Carbon/Alginate/Nanocellulose-Fe Composite as Slow Release Fertilizer - Cahyati, Riska; Syahirah, Atikah nur; Rahmah, Siti; Muchtar, Zainuddin; Jasmidi, Jasmidi; Pulungan, Ahmad Shafwan; Zubir, Moondra; Selly, Rini; Faradilla, Putri (Indonesian Journal of Chemical Science and Technology (IJCST), 2023)
Fe deficiency in plants results in yellowing of leaves on plants and also reduces the quality of fruit produced. Fe deficiency in plants can be treated by applying slow release fertilizer which will release the nutrients in the fertilizer slowly according to plant needs so that there will be no problem of deficiency or excess of Fe. Activated Carbon/Alginate/Nanocellulose-Fe Composite can be used as slow release fertilizer because this composite releases Fe slowly with citric acid medium and tested with AAS. The functional groups in the Activated Carbon/Alginate/Nanocellulose-Fe Composite showed no disappearance of the functional groups belonging to activated carbon, alginate or nanocellulose so that it can be said that these three components were successfully made into composites and can be carriers of nutrients in micro-fertilizers.